Bone tissue engineering with a collagen–hydroxyapatite scaffold and culture expanded bone marrow stromal cells. Issue 2 (7th June 2014) - Villa, Max M.; Wang, Liping; Huang, Jianping; Rowe, David W.; Wei, Mei
Abstract Osteoprogenitor cells combined with supportive biomaterials represent a promising approach to advance the standard of care for bone grafting procedures. However, this approach faces challenges, including inconsistent bone formation, cell survival in the implant, and appropriate biomaterial degradation. We have developed a collagen–hydroxyapatite (HA) scaffold that supports consistent osteogenesis by donor‐derived osteoprogenitors, and is more easily degraded than a pure ceramic scaffold. Herein, the material properties are characterized as well as cell attachment, viability, and progenitor distribution in vitro. Furthermore, we examined the biological performance in vivo in a critical‐size mouse calvarial defect. To aid in the evaluation of the in‐house collagen–HA scaffold, the in vivo performance was compared with a commercial collagen–HA scaffold (Healos®, Depuy). The in‐house collagen–HA scaffold supported consistent bone formation by predominantly donor‐derived osteoblasts, nearly completely filling a 3.5 mm calvarial defect with bone in all samples (n = 5) after 3 weeks of implantation. In terms of bone formation and donor cell retention at 3 weeks postimplantation, no statistical difference was found between the in‐house and commercial scaffold following quantitative histomorphometry. The collagen–HA scaffold presented here is an open and well‐defined platform that supports robust bone formation and should facilitate the further development of collagen–hydroxyapatite biomaterials for bone tissue engineering. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 243–253, 2015.